Challenges of overcoming ageism towards elderly people in healthcare context - Nowakowska, Iwona (Horyzonty Wychowania, 2018)
RESEARCH OBJECTIVE: The purpose of the paper is to analyse the impact ageism may have on providing healthcare to elderly people.THE RESEARCH PROBLEM AND METHODS: The article investigates the consequences of ageism in medical settings, where the elderly are particularly vulnerable to discrimination, distinguishing ageism from appropriate practice variation as well as giving suggestions to improve the situation. The paper analyses research published worldwide on selected issues connected with ageism with special attention to medical professionals’ attitudes and ageist behaviours of the elderly’s environment in a situation of their disability or illness.THE PROCESS OF ARGUMENTATION: Firstly, the relation of ageism to other forms of stereotyping is outlined. Then, the threats of positive ageism are elaborated. The next section is devoted to self-stereotyping of the elderly and its impact on their functioning. Then, the paper discusses medical professionals’ attitudes and ways to measure them, as well as educational interventions that may alter them. Finally, the article refers effective ways of adjusting health promotion messages to the needs of older adults.RESEARCH RESULTS: Ageism bases on mechanisms similar to sexism and racism, but there are some remarkable differences. Positive ageism may be compassionate, however, might be harmful when intruding into an elderly person’s decisions. Self-stereotyping may be described with a model of a vicious cycle. Contact with the elderly is found to be useful in changing medical staff’s attitudes. Family-centred messages are most effective when it comes to health promotion among older adults.CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: Studies on ageism prove that negative convictions about the elderly are harmful and affect their functioning. Inclusion of the elderly should be applied in social contexts as well as in science, as the elderly are often missed out in research samples.